The Use Reproductive Health Game (KEPO Game) on Female Adolescent’s Five Dimensions Satisfaction - Susilawati, Sri; Husin, Farid; Wirakusumah, Firman Fuad; Dhamayanti, Meita; Herman, Herry; Anwar, Ruswana; Sekarwana, Nanan (Global Medical & Health Communication (GMHC), 2019)
The adolescent’s reproductive health is the major problem that should take into consideration. To solve this problem, it needs an alternative strategy by using a media, reproductive health/kesehatan reproduksi (KEPO) game, in Android smartphone. The aim is analyzing the effect of KEPO game on the five dimensions of female adolescent’s satisfaction. The research method was quasi-experiment, and the research design used pre-test post-test with control group design. The sampling technique used simple random sampling. The subject was 64 respondents of female student age of 12−15 years old in public junior high school in Bandung city. The respondents divided into two groups, the first one treated by KEPO game is 32 students of Public Junior High School 50 Bandung, while the control group was 32 students of Public Junior High School 8 Bandung, get counseling from Ujungberung Indah Public Health Center; the entire research conducted in April−May 2017. Research result shows the percentage differential of satisfaction average score improvement on both groups. The treatment group produces percentage of content 14.6%, display 23.6%, accuracy 11.4%, easiness 12.4%, and correctness 17%. In the other hand, control group produces content 5%, display 3%, accuracy 4.3%, easiness 2.8%, and correctness 4.7% with a p value for each indicator was p<0.05 on the intervention group and p<0.05 on the control one. Entirely, it known that adolescent’s satisfaction from those five aspects in using KEPO game has a matter differential p<0.05, with satisfied percentage, was 84%. In conclusion, there was an effect of KEPO game on the five dimensions of female adolescent’s satisfaction. PENGARUH PENGGUNAAN GIM KESEHATAN REPRODUKSI (KEPO) TERHADAP LIMA DIMENSI KEPUASAN REMAJA PEREMPUANKesehatan reproduksi remaja merupakan masalah utama yang harus diperhatikan sehingga untuk mengatasi ketidakpuasan remaja, diperlukan strategi alternatif, yaitu gim kesehatan reproduksi (KEPO) menggunakan smartphone Android. Tujuan penelitian ini adalah menganalisis pengaruh gim KEPO terhadap lima dimensi kepuasan remaja perempuan. Metode penelitian adalah quasi-experiment dan desain penelitian menggunakan pre-test post-test with control group design. Teknik pengambilan sampel menggunakan simple random sampling. Subjek penelitian adalah 64 responden siswa perempuan usia 12–15 tahun SMP Negeri di Kota Bandung. Responden dibagi menjadi dua kelompok, yaitu kelompok perlakuan menggunakan gim KEPO sebanyak 32 siswa SMP Negeri 50 Bandung, sedangkan kelompok kontrol menerima penyuluhan dari Puskesmas Ujungberung Indah sebanyak 32 siswa SMP Negeri 8 Bandung. Penelitian dilaksanakan pada bulan April–Mei 2017. Hasil penelitian menunjukkan perbedaan persentase peningkatan nilai rerata kepuasan pada kedua kelompok. Kelompok perlakuan menghasilkan persentase konten 14,6%, tampilan 23,6%, akurasi 11,4%, kemudahan 12,4%, dan ketepatan 17%. Di sisi lain, kelompok kontrol menghasilkan konten 5%, tampilan 3%, akurasi 4,3%, kemudahan 2,8%, dan ketepatan 4,7% dengan nilai p untuk setiap indikator sebesar p<0,05 pada kelompok intervensi dan p>0,05 kelompok kontrol. Secara keseluruhan, diketahui bahwa kepuasan remaja dari kelima aspek kepuasan dalam menggunakan gim KEPO memiliki perbedaan yang bermakna p<0,05 dengan persentase puas 84%. Simpulan, terdapat pengaruh penggunaan gim KEPO terhadap lima dimensi kepuasan remaja perempuan.